Children Facial Expression Production: Influence of Age, Gender, Emotion Subtype, Elicitation Condition and Culture - Grossard, Charline; Chaby, Laurence; Hun, Stéphanie; Pellerin, Hugues; Bourgeois, Jérémy; Dapogny, Arnaud; Ding, Huaxiong; Serret, Sylvie; Foulon, Pierre; Chetouani, Mohamed; Chen, Liming; Bailly, Kevin; et al. (Frontiers in Psychology, 2018)
The production of facial expressions is an important skill that allows children to share and adapt emotions with their relatives and peers during social interactions. These skills are impaired in children with Autism Spectrum Disorder. However, the way in which typical children develop and master their production of facial expressions has still not been clearly assessed. This study aimed to explore factors that could influence the production of facial expressions in childhood such as age, gender, emotion subtype (sadness, anger, joy, neutral), elicitation task (on request, imitation), area of recruitment (French Riviera and Parisian) and emotion multimodality. A total of one hundred fifty-seven children aged 6 to 11 years were enrolled in Nice and Paris, France. We asked them to produce facial expressions in two different tasks: imitation with an avatar model and production on request without a model. Results from a multivariate analysis revealed that: (1) children performed better with age. (2) Positive emotions were easier to produce than negative emotions. (3) Children produced better facial expression on request (as opposed to imitation); and (4) Riviera children performed better than Parisian children suggesting regional influences on emotion production. We conclude that facial emotion production is a complex developmental process influenced by several factors that needs to be acknowledged in future research.